(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article reflects some modern features of the implementation of the internal control system of economic entities. The topic is relevant, since internal control is currently a tool with which an economic entity can not only survive the economic crisis, but also improve. The result of the article is the author’s proposals, the implementation of which will improve the studied area in each company.